TANGGUNG GUGAT PERSEROAN TERBATAS KBS ATAS PEMUTUSAN KONTRAK SECARA SEPIHAK KEPADA PERSEROAN TERBATAS ASIP BERDASARKAN KITAB UNDANG-UNDANG HUKUM PERDATA - Rahmita Suryani (CALYPTRA, 2014)
Agreement or contract is an event where someone promised to another person or in which two men were each promised to implement something . Agreement made by the parties for the purpose they want to achieve . ( Article 1313 Civil Code, Civil Code ). Bank guarantees are guarantees given by the banks in terms of the bank stating that the contents of a written acknowledgment agreeing to adhere to the insured in a certain period of time and under certain conditions in the future if it turns out is guaranteed not fulfill its obligations to guarantee the recipient . Agreements that use the services of the bank as an agreement by PT . ASIP and PT . KBS. Agreement made by the parties to use the bank guarantee as collateral to PT. KBS if PT. ASIP does not fulfill the agreement.